PENGARUH MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP KETERAMPILAN LAY-UP SHOOT BOLA BASKET - Davi Sofyan (Universitas Majalengka, 2020)
The purpose of this study was to determine how much influence the cooperative learning model type student team's achievement division has on basketball shoot lay-up skills. The research method used in this research is a quasi-experimental method. The type of research design used was the non-equivalent group design. The population in this study were students of class XI SMA Negeri 1 Majalengka in 2019 totaling 424 students. The sampling technique used in this study was cluster random sampling technique. The sample in this study amounted to 214 students consisting of class XI IPS 1-4 and XI MIPA 7-8. The experimental group class XI IPS 1-2 and XI MIPA, control group class XI IPS 3-4 and XI MIPA 8. The results showed that the mean pre-test lay-up shoot of the experimental group was 4.09 while the control group was 3.92. The mean post-test shoot lay-up of the experimental group was 6.76 while the control group was 4.72. Furthermore, by looking at 95% confidence interval of the difference, there is a difference between the shoot lay-up results of the experimental group and the control group, which is -0.190 to 2.412. Thus, it can be concluded that STAD is effective in improving basketball shoot lay-up skills.